Effectiveness of Student Academic Policy Orientation of the Bachelor of Science in Economics Program, Bicol University College of Business, Economics and Management - Bongat, Clea L. (Future Science / FSH-PH Publications, 2025)
This study examines the effectiveness of Academic Orientation Programs for incoming freshmen, shifters, and transferees in a col-lege setting. The program is designed to familiarize students with the school environment, policies, rules, and the socio-cultural cli-mate, helping them navigate academic life. The study assessed stu-dents’ knowledge levels before and after the orientation using a pre-test and post-test, with a control group of students who did not par-ticipate in the orientation for comparison.Results revealed that students in the experimental group (those who participated in the orientation) had an average knowledge level before the orientation, which improved significantly after the pro-gram. Post-test scores indicated a notable increase in students' un-derstanding of academic policies, suggesting that the orientation had a positive effect on their knowledge. In contrast, students in the control group, who did not undergo the orientation, showed no sig-nificant improvement in their knowledge of academic policies. This comparison strengthens the conclusion that the orientation pro-gram effectively enhanced students’ understanding of the school’s academic environment. Common mistakes related to academic poli-cies, procedures, and programs were identified in both groups, with the experimental group making fewer errors after the orientation.The study recommends strategies to enhance the orientation program, including conducting a pre-assessment of student needs, developing relevant materials, employing a holistic delivery ap-proach, and ensuring continuous evaluation. It also suggests that integrating orientation content consistently into classroom policies and course offerings can reinforce students’ understanding.The study concludes that regular and reinforced orientation pro-grams are crucial for improving students' knowledge of academic policies. The inclusion of a control group reinforces the effectiveness of the orientation program, and further research is encouraged to explore additional factors influencing the effectiveness of orienta-tion and its impact on students’ academic success.